Hba1c Levels with Urine Microalbumin in Type 2 Diabetes Mellitus Patients - Luki Marliani; Harsismanto J (Jurnal Keperawatan Silampari, 2026)
This study aimed to determine the correlation between HbA1c levels and microalbuminuria in patients with type 2 diabetes mellitus at the Karang Tinggi Community Health Center. This study used a cross-sectional design. The results showed a positive and significant correlation, categorized as low correlation, between HbA1c levels and microalbuminuria in patients with type 2 diabetes mellitus, with a 2-tailed p-value of 0.031 and a correlation coefficient (r) of 0.333. In conclusion, higher HbA1c levels are associated with higher levels of microalbuminuria.   Keywords: Diabetes Mellitus, Diabetic Nephropathy, HbA1c, Microalbuminuria